To aitch or not to aitch: Ripogonum (Ripogonaceae) or Rhipogonum (Rhipogonaceae)?. Issue 3 (28th December 2018) - Seberg, Ole; Petersen, Gitte; Wagner, Peter
Abstract: For over 150 years, the correct spelling of the genus name Ripogonum ( Rhipogonum ) and the derived family name Ripogonaceae ( Rhipogonaceae ) has been the subject of uncertainty. The different spellings in use are due to transliterations of the Greek letter "ρ" (rho with spiritus asper) into Latin as either "r" or "rh". As neither of Ripogonum or Rhipogonum can be considered incorrect, priority must be given to the original spelling of the name used, Ripogonum . Therefore, Ripogonaceae is the correct spelling for the family name.